Differential structures and enterotype-like clusters of Bifidobacterium responses to probiotic fermented milk consumption across subjects using a Bifidobacterium-target procedure - Bai, Xiaoye; Shen, Lingling; Gao, Xu; Yu, Zhongjie; Sakandar, Hafiz Arbab; Kwok, Lai-Yu; Sun, Zhihong (Food research international, 2021)
[Display omitted] •The Bifidobacterium diversity in gut was explored by Bifidobacterium-target procudure.•Baeline intestinal Bifidobacterium determine the response for the probiotic fermented milk (PFM).•High-load intestinal Bifidobacterium adolescentis was less likely to be interfered by PFM. The health-promoting attributes of bifidobacteria have piqued interest of researchers worldwide. However, scant published studies are available pertinent to bifidobacteria in microbiota/metagenomics datasets due to its intrinsic low abundance and limitations of detection methods. In this work, we designed a procedure to optimize the detection of the bifidobacterial population in complex biological samples with single-molecule real-time sequencing (SMRT) technology, including one primer pair designated as Bif-6 and a Bifidobacterium-specific database. The optimized procedure detected 14 bifidobacterial species/subspecies in ten human stool samples (2024 sequences per sample) and eight breast milk samples (3473 sequences per sample), respectively. Furthermore, by using the optimized procedure of SMRT, we investigated the effect of a 4-week-intervention of probiotic fermented milk (PFM; 200 g/day) on the gut bifidobacteria population of adults. The results showed that consuming PFM changed the structure and enterotype-like clusters of Bifidobacterium. After the consumption of PFM, the level of gut Bifidobacterium animalis increased significantly, replacing several originally dominating taxa in some subjects, including B. catenulatum, B. breve, and B. bifidum. On the other hand, B. adolescentis was, unaffectedly, the representative species in subjects having an original enterotype-like cluster of B. adolescentis. In conclusion, our work designed a procedure for detecting the bifidobacterial population in complex samples. By applying the currently designed procedure, we found that the PFM intervention changed the bifidobacterial enterotype-like cluster of some subjects, and such change was dependent on the basal bifidobacterial population.